HUBUNGAN TINGKAT SOSIAL EKONOMI ORANGTUA DENGAN KEMANDIRIAN BELAJAR SISWA KELAS X SMA NEGERI 1 BINJAI KABUPATEN LANGKAT TAHUN PELAJARAN 2017/2018 - Sari Wardani Simarmata; Kurniawati Kurniawati (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
The purpose of this study is to determine the relationship of socio-economic level of parents with learning independence students of Class X SMA Negeri 1 Binjai Kabupaten Langkat Lesson Year 2017/2018, with a population of 252 students, consists of 7 classes a sample is 49. This type of research used in this research is quantitative Correlation method. The instrument used is to spread the scale of the entire sample as inputs to determine the actual situation in the SMA Negeri 1 Binjai Kabupaten Langkat, and analysis of data using Product Moment Correlation test. From the test results hypothesis that the value r arithmetic> r table is 0.895> 0.281, so it is taken a conclusion that there is a relationship Level of socio-economic parent with independence Learning Students class X SMA Negeri 1 Binjai Kabupaten Langkat Lesson Year 2017/2018. Suggestions for future researchers to better pay attention to other psychological aspects of a student, such as self-control, emotional intelligence, while also considering more effective research time, and need to improve the quality of cooperation with parents even though the intensity of meeting and distance with the parents of students to be a bit of a constraint so that the problems faced by students is not just a responsibility of the school.Keywords: Level of Socio-Economic Parents, Learning Independence